2020
DOI: 10.1101/2020.08.21.261941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of thymidine auxotrophicAgrobacterium tumefaciensstrains for plant transformation

Abstract: Agrobacterium-mediated transformation is a widely used gene delivery method for fundamental researches and crop trait improvement projects. Auxotrophic Agrobacterium tumefaciens strains are highly desirable for plant transformation because they can be easily removed from the explants after co-cultivation due to their dependence on essential nutrient supplementation. The thymidine auxotrophic A. tumefaciens strain LBA4404Thy- has been successfully used for plant transformation, however, auxotrophic version of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The auxotrophic Agrobacterium strains rely on thymidine for growth and are thus highly advantageous because it allows for much better control of Agrobacterium overgrowth after the co-cultivation stage ( Aliu et al, 2020 ). Agrobacterium will also less likely persist in callus or regenerated plants because of its dependence on thymidine for survival which is not supplemented in plant culture media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The auxotrophic Agrobacterium strains rely on thymidine for growth and are thus highly advantageous because it allows for much better control of Agrobacterium overgrowth after the co-cultivation stage ( Aliu et al, 2020 ). Agrobacterium will also less likely persist in callus or regenerated plants because of its dependence on thymidine for survival which is not supplemented in plant culture media.…”
Section: Discussionmentioning
confidence: 99%
“…A thymidine auxotrophic (Thy-) version of the Agrobacterium strains of LBA4404 ( Lowe et al, 2016 ; kindly provided by Dr. William Gordon-Kamm of Corteva Agriscience) and EHA105 ( Aliu et al, 2020 ) were used to harbor the binary vector construct PHP93739. Both Agrobacterium strains contain the ternary helper plasmid PHP71539 to increase virulence ( Anand et al, 2018 ; kindly provided by Dr. William Gordon-Kamm of Corteva Agriscience).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the potential benefits of using auxotrophic strains of Agrobacterium , such strains are generally not available in the public sector. Towards that end, Aliu et al (2020) used homologous recombination to develop thymidine auxotrophs of strains EHA101, EHA105, and EHA105D. Transient GUS expression assays using hyper-transformable seedlings (Wu et al, 2014) of arabidopsis showed that, except for EHA105D, auxotrophic strains can deliver T-DNA at comparable levels to the parental strains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being a thymidine auxotroph, EHA105D has a deleted atsD gene, which is implicated in plant cell attachment. However, the LBA4404Thy-auxotroph remained the most effective strain (Aliu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation